One-Step Automatic Radiosynthesis and Evaluation of [18F]TM-30089 as GPR44 Radiotracer - Jiangling Peng; Wei Tang; Jeffrey Rawson; Lynn Miao; Nelson Gonzalez; Runkai Yin; Jiaqi Chen; Melinda Ji; Zhixuan Li; Anna Gao; Andy Z. Wu; John E. Shively; et al. (MDPI AG, 2023)
Recently, a G-protein coupled receptor 44 (GPR44) was discovered to play a significant role in the process of inflammation-related diseases, including cancer and diabetes. However, the precise role of GPR44 has yet to be fully elucidated. Currently, there is a strong and urgent need for the development of GPR44 radiotracers as a non-invasive methodology to explore the exact mechanism of GPR44 on inflammation-related diseases and monitor the progress of therapy. TM-30089 is a potent GPR44 antagonist that exhibits a high specificity and selectivity for GPR44. Its structure contains a fluorine nuclide, which could potentially be replaced with 18F. In the present study, we successfully took a highly effective synthesis strategy that pretreated the unprotected carboxylic acid group of the precursor and developed a feasible one-step automatic radiosynthesis strategy for [18F]TM-30089 with a high radiochemical purity and a good radiochemical yield. We further evaluated this radiotracer using mice models implanted with 1.1 B4 cell lines (GPR44-enriched cell lines) and human islets (high GPR44 expression), respectively. The results revealed the persistent and specific uptake of [18F]TM-30089 in GPR44 region, indicating that [18F]TM-30089 is a promising candidate for targeting GPR44. Further evaluation is ongoing.